2023
DOI: 10.1038/s41561-023-01218-y
|View full text |Cite
|
Sign up to set email alerts
|

Glacier retreat alters downstream fjord ecosystem structure and function in Greenland

Abstract: The melting of the Greenland Ice Sheet is accelerating, with glaciers shifting from marine to land termination and potential consequences for fjord ecosystems downstream. Monthly samples in 2016 in two fjords in southwest Greenland show that subglacial discharge from marine-terminating glaciers sustains high phytoplankton productivity that is dominated by diatoms and grazed by larger mesozooplankton throughout summer. In contrast, melting of land-terminating glaciers results in a fjord ecosystem dominated by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Our observation of low surface water pCO 2 in coastal Greenland waters affirm the previous conclusions of Sejr et al (2011Sejr et al ( , 2014, Meire et al (2015Meire et al ( , 2023, and Rysgaard et al ( 2012) that these waters are large CO 2 sinks. We measured ∆pCO2 values ranging from -295 to 5 µatm with an average of -127 µatm.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our observation of low surface water pCO 2 in coastal Greenland waters affirm the previous conclusions of Sejr et al (2011Sejr et al ( , 2014, Meire et al (2015Meire et al ( , 2023, and Rysgaard et al ( 2012) that these waters are large CO 2 sinks. We measured ∆pCO2 values ranging from -295 to 5 µatm with an average of -127 µatm.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, freshwater-driven circulation dynamics play a pivotal role in dictating the location and intensity of biological DIC consumption, thereby impacting the magnitude of air-sea exchange. Indeed, a recent study found that neighboring fjords with different glacial termini showed double the carbon uptake near MTGs compared to near LTGs (Meire et al, 2023). This relationship is evident in West Greenland, where the spatial distribution of AOU closely corresponds to the distribution of surface layer pCO 2 values (Fig.…”
Section: Glacial Meltwater Lowers Pco 2 Levels Along the Coasts Of Gr...mentioning
confidence: 71%
See 2 more Smart Citations
“…This influx of OC has the potential to release additional CO 2 into the atmosphere, thereby influencing the dynamics of the active carbon cycle 25 . Furthermore, the increased influxes of land-derived OC could alter ecosystem structure and function in Svalbard fjords, as demonstrated in Greenland fjords 64 .…”
Section: Discussionmentioning
confidence: 99%